Network analysis of ecological momentary assessment identifies frustration as a central node in irritability - Tseng, Wan‐Ling; Naim, Reut; Chue, Amanda; Shaughnessy, Shannon; Meigs, Jennifer; Pine, Daniel S.; Leibenluft, Ellen; Kircanski, Katharina; Brotman, Melissa A. (Journal of child psychology and psychiatry, 2023)
Background Irritability presents transdiagnostically, commonly occurring with anxiety and other mood symptoms. However, little is known about the temporal and dynamic interplay among irritability‐related clinical phenomena. Using a novel network analytic approach with smartphone‐based ecological momentary assessment (EMA), we examined how irritability and other anxiety and mood symptoms were connected. Methods Sample included 152 youth ages 8–18 years (M ± SD = 12.28 ± 2.53; 69.74% male; 65.79% White) across several diagnostic groups enriched for irritability including disruptive mood dysregulation disorder (n = 34), oppositional defiant disorder (n = 9), attention‐deficit/hyperactivity disorder (n = 47), anxiety disorder (n = 29), and healthy comparisons (n = 33). Participants completed EMA on irritability‐related constructs and other mood and anxiety symptoms three times a day for 7 days. EMA probed symptoms on two timescales: “since the last prompt” (between‐prompt) versus “at the time of the prompt” (momentary). Irritability was also assessed using parent‐, child‐ and clinician‐reports (Affective Reactivity Index; ARI), following EMA. Multilevel vector autoregressive (mlVAR) models estimated a temporal, a contemporaneous within‐subject and a between‐subject network of symptoms, separately for between‐prompt and momentary symptoms. Results For between‐prompt symptoms, frustration emerged as the most central node in both within‐ and between‐subject networks and predicted more mood changes at the next timepoint in the temporal network. For momentary symptoms, sadness and anger emerged as the most central node in the within‐ and between‐subject network, respectively. While anger was positively related to sadness within individuals and measurement occasions, anger was more broadly positively related to sadness, mood lability, and worry between/across individuals. Finally, mean levels, not variability, of EMA‐indexed irritability were strongly related to ARI scores. Conclusions This study advances current understanding of symptom‐level and temporal dynamics of irritability. Results suggest frustration as a potential clinically relevant treatment target. Future experimental work and clinical trials that systematically manipulate irritability‐related features (e.g. frustration, unfairness) will elucidate the causal relations among clinical variables.